Konsep Dasa Paramartha pada Karakterisasi Tokoh Aji Dharma dalam Pertunjukan Wayang Tantri oleh I Wayan Wija - I Dewa Ketut Wicaksandita; Hendra Santosa; I Ketut Sariada (Dance and Theatre Review, 2020)
The Concept of Dasa Paramartha on the Characterization of Aji Dharma in a Wayang Tantri Performance by I Wayan Wija. Dasa Paramartha, as the teachings of dharma (goodness) in Hinduism, then becomes a material that is flexible enough to be displayed in broadcasting the meaning and value of ethical, moral, and social behavior education. Wayang Tantri, in the play of Sang Aji Dharma Kepastu presents the character of Prabu Aji Dharma with the characteristics trait displayed as a figure of dharma who later becomes a role model for Wayang Tantri audiences. This study aims to reveal the values of Dasa Parartha’s teachings in the characterization of Aji Dharma figures. The qualitative descriptive method with data collection in the form of observation, interviews, and study documentation of the Wayang Tantri video of Sang Aji Dharma Kepastu with a duration of approximately 2 hours, then analyzed by, The Aesthetic Pedalangan Theory supported by Semiotic Theory. The results of the research are the representation of the teachings of Dasa Parmartha, which is in the form of Tapa: physical and mental self-control; Bharata: curb lust; Samadhi: mental concentration on God; Santa: being calm and honest; Sanmata: aspiring and aiming towards goodness; Karuna: affection between living beings; Karuni: compassion for plants, goods and so on; Upeksa: being able to distinguish right from wrong, good and bad; Mudhita: trying to please others; and Maitri: eager to seek friendship based on mutual respect.Keywords: representation; Dasa Paramartha; Aji Dharma; Wayang Tantri